Teknologi Tepat Guna Pembuatan Gula Aren Kristal Di Desa Mabodo Kecamatan Kontunaga Kabupaten Muna Sulawesi Tenggara - Asranudin, Asranudin; Holilah, Holilah; Sadimanatara, Muh. Syukri; Karimuna, La; Ernawati Harfi, Wa Ode; Josaphat, Josaphat (Jurnal Pengabdian Masyarakat Ilmu Terapan (JPMIT), 2019)
Southeast Sulawesi is a region that rich in various agricultural products including cocoa commodities which are widely known to foreign countries. Southeast Sulawesi is divided into two regions, namely the land divided into nine and the islands divided into eight administrative regions. Muna is the Southeast Sulawesi archipelago rich in various agricultural products, especially from sugar palm plants. Specifically, palm sugar is abundant in Mabodo with a plant density of 30m2 so that it has the potential to develop various diversified products. The technology transfer applied to PPTTG activities was a method or process of palm sugar processing into organic crystal sugar. The purpose of the PPTTG was to apply appropriate technology through the stages of Participatory Rural Appraisal (PRA), participatory Technology Development, community development, Persuasive to Educational. To maintain the existence of PPTTG in Mabodo Village, product assistance was carried out such as design and registration of trademark IPRs, packaging. Packaging of product distribution licenses and product socialization to local government stakeholders. In this activity, it can be seen that all the women who are members of â€œKelompok Usaha Nira Sejahtera Mabodoâ€ have been skilled in crystallizing of the roomie manually or with crystallizers. This success has opened the gap for the presence of new MSME centers that produce a variety of palm-based diversified products. Eventhough their entrepreneurial spirit was intrigued through their curiosity to process other parts of the sugar palm plant into food products or crafts of high economic value that will sustain the family economy. The sustainability of the technology and products of PPTTG activities requires evaluation and assistance for the next few years that can bring Mabodo Village to become the Aren Tourism Area.